Forgotten wives : how women get written out of history - Oakley, Ann (Book collections on Project MUSE., 2021)
Forgotten Wives examines how marriage has contributed to the active 'disremembering' of women's achievements. Ann Oakley uses case studies of four women married to well-known men to ask questions about gender inequality and contributes a fresh vision of how the welfare state developed in the early 20th century.